Heat distribution simulation of a phase change memory with separated heater structure / Mohd Shariman A. Aziz - A. Aziz, Mohd Shariman (2019)
Phase change memory (PCM) is a type of the non-volatile memory. A PCM structure with the heater layer was more efficient in heating up the PCM material. Typically, the heater needs to maintain in a fairly high temperature because enough power were enquired in ensuring the melting temperature to be reached. Therefore, the Silicon Carbide (SiC) was proposed as the heater layer. SiC’s advantages was low thermal expansion, high thermal conductivity, excellent thermal shock resistance and wide band gap material. The objective of this study were to determine the optimum temperature for the changes in the memory layer using SiC as the heater layer by simulation method, to investigate the ability of SiC as a heater layer in separate-heater PCM structure to change the phase change material properties from amorphous to crystalline state by simulation method and to determine the power consumption for the phase change memory (PCM) and investigated multilevel storage of the phase change memory (PCM) by calculating the resistance changes of the memory layer.